1981
DOI: 10.1177/001316448104100238
|View full text |Cite
|
Sign up to set email alerts
|

A Construct Validation Study of the Fennema-Sherman Mathematics Attitudes Scales

Abstract: The Fennema-Sherman Mathematics Attitudes Scales were administered to 1541 junior high school students. To investigate the construct validity of the scales, factor analyses were performed on the responses to the 108 items comprising the scales. Additional factor analyses of the scale scores were performed, and a comparison was made with results reported by Fennema and Sherman (1976). Analysis of the items led to the interpretation of eight factors. The results generally provided empirical evidence to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The separation of different subscales is commonly used in the field of education, as seen with the use of individual subscales from the Fennema–Sherman Mathematics Attitudes Scales (Fennema & Sherman, ) in studies related to mathematics (Iben, ; O'Neal, Ernest, McLean, & Templeton, ). The Fennema–Sherman subscales have been validated when the instrument has been used in part (O'Neal et al, ) or as a whole (Broadbooks, Elmore, Pedersen, & Bleyer, ). The subscales used in this study are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The separation of different subscales is commonly used in the field of education, as seen with the use of individual subscales from the Fennema–Sherman Mathematics Attitudes Scales (Fennema & Sherman, ) in studies related to mathematics (Iben, ; O'Neal, Ernest, McLean, & Templeton, ). The Fennema–Sherman subscales have been validated when the instrument has been used in part (O'Neal et al, ) or as a whole (Broadbooks, Elmore, Pedersen, & Bleyer, ). The subscales used in this study are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The subscale includes 12 items scored on a 5-point Likert scale ("strongly disagree" to "strongly agree"). The Fennema-Sherman scale has been used in many studies and has shown excellent psychometric qualities (Broadbooks, Elmore, Pedersen, & Bleyer, 1981;Hyde, Fennema, Ryan, Frost, & Hopp, 1990;Mulhern & Rae, 1998;Tocci & Engelhard, 1991). Moreover, studies that adapted this scale to measure attitudes toward science also revealed very good psychometric properties (Bazler, Spokane, Ballard, & Fugate, 1993;Collier, Spokane, & Bazler, 1998;Levin & Fowler, 1984).…”
Section: Gender Stereotype Endorsement Scalementioning
confidence: 99%
“…A subsequent factor analytic study of the FSMAS by Broadbooks, Elmore, Pedersen, and Bleyer (1981) on the eight scales (excluding Anxiety) for females and males both individually and together yielded only one factor, while a similar analysis by them of all nine scales yielded only two factors. However, their item-level analysis of the FSMAS did identify eight factors that basically supported the theoretical structure of domain-specific scales as described by Fennema and Sherman (1976a).…”
mentioning
confidence: 92%